2018
DOI: 10.1176/appi.neuropsych.17060117
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Factors Linked to Adherence and Short-Term Outcome in a U.S. Functional Neurological Disorders Clinic: A Retrospective Cohort Study

Abstract: Despite advancements in the assessment and management of functional neurological disorder (FND), the feasibility of implementing a new standard of care remains unclear. Chart reviews were performed for 100 patients with motor FND to investigate factors related to treatment adherence and clinical improvement over an average follow-up of 7 months. Of 81 patients who returned for follow-up, a history of chronic pain disorder inversely correlated with improvement. Of the 50 individuals newly referred for treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 57 publications
1
22
0
1
Order By: Relevance
“…Once a patient and the immediate family are receptive to the diagnosis, the core components of treatment for functional dystonia and related functional motor symptoms include physical interventions (e.g., physical therapy, occupational therapy), [28][29][30] psychological interventions (including a component of cognitive-behavioral therapy [CBT] to explore the interactions between functional neurological symptoms, thoughts, behaviors, emotions, and psychosocial factors), 31,32 and management of comorbid psychiatric and somatic (e.g., pain, fatigue) symptoms that may have prognostic implications. [33][34][35] While the above components are core aspects of treatment, the identification of patient-specific predisposing vulnerabilities, acute precipitants, and perpetuating factors should be elucidated to help individualize treatments with these factors in mind. 36 In this case, predisposing vulnerabilities included early-life separation anxiety, dyslexia with academic difficulties, bullying at school, tendency to not verbalize stress and affective symptoms to supports, and the concurrent presence of another functional somatic disorder (irritable bowel syndrome).…”
Section: Questions To the Consultantsmentioning
confidence: 99%
“…Once a patient and the immediate family are receptive to the diagnosis, the core components of treatment for functional dystonia and related functional motor symptoms include physical interventions (e.g., physical therapy, occupational therapy), [28][29][30] psychological interventions (including a component of cognitive-behavioral therapy [CBT] to explore the interactions between functional neurological symptoms, thoughts, behaviors, emotions, and psychosocial factors), 31,32 and management of comorbid psychiatric and somatic (e.g., pain, fatigue) symptoms that may have prognostic implications. [33][34][35] While the above components are core aspects of treatment, the identification of patient-specific predisposing vulnerabilities, acute precipitants, and perpetuating factors should be elucidated to help individualize treatments with these factors in mind. 36 In this case, predisposing vulnerabilities included early-life separation anxiety, dyslexia with academic difficulties, bullying at school, tendency to not verbalize stress and affective symptoms to supports, and the concurrent presence of another functional somatic disorder (irritable bowel syndrome).…”
Section: Questions To the Consultantsmentioning
confidence: 99%
“… 21 , 22 Here, we provide a framework for the initial assessment and management of mFND modeled in part after the example of the Massachusetts General Hospital FND Clinic. 6 , 23 – 26 Using the approach detailed below, Glass et al previously reported in 81 consecutive patients with at least one follow-up that 42% noted some degree of clinical improvement at 7 months. 23 While emphasis on neurological examination and semiological features aids the neurologist’s role in diagnosis, a comprehensive assessment guiding the development of a patient-centered treatment plan benefits from interdisciplinary neurologic, psychiatric, allied mental health and rehabilitation perspectives.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 23 – 26 Using the approach detailed below, Glass et al previously reported in 81 consecutive patients with at least one follow-up that 42% noted some degree of clinical improvement at 7 months. 23 While emphasis on neurological examination and semiological features aids the neurologist’s role in diagnosis, a comprehensive assessment guiding the development of a patient-centered treatment plan benefits from interdisciplinary neurologic, psychiatric, allied mental health and rehabilitation perspectives. 14 Sections of this article outline the neuropsychiatric history, physical examination, delivery of the diagnosis, treatment planning, physical rehabilitation, and psychological treatments.…”
Section: Introductionmentioning
confidence: 99%
“…female predominance, high rates of depression-anxiety and adverse life event burden (Guz et al, 2004; Paras et al, 2009; Taylor, 2003)) further raising the possibility of a partially overlapping biology. Comorbid somatic symptoms in patients with FND also negatively impact healthcare utilization and prognosis (Ettinger et al, 1999; Glass et al, 2018; Ibrahim et al, 2009; Salinsky et al, 2016).…”
Section: Introductionmentioning
confidence: 99%